PENGARUH IKLIM ORGANISASI DAN MOTIVASI KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN INDOMARET SE-KECAMATANBULELENG - KOMANGTRISNA SARI DEWI; LUH PUTU LAURA HERMAWATI (Universitas Mahasaraswati K. Mataram, 2024)
The purpose of this research is to find out how organizational climate and work motivation influence Organizational Citizenship Behavior with job satisfaction as anintervening variableforIndomaret employees in Buleleng District. This study uses a quantitative approach. The data collection techniques used in this research are documentation, interviews and questionnaires. The population in this study was all Indomaret employees in Buleleng District, namely 115 people and the sample 8 in this study was calculated using the Slovin formula and then using proportional random sampling, namely by taking53 samples. The analysis technique used in this researc his avariance-based structural equation model(SEM) or component based SEM,whichis known as Partial Least Square (PLS). The results of this research show that organizational climate has a positive and significant effect on job satisfaction,work motivation hasa positive and significant effect on job satisfaction, organizational climate has a positive and significant effect on Organizational Citizenship Behavior, work motivation has a positive and significant effect on Organizational Citizenship Behavior, job satisfaction has an effect positive and significant on Organizational Citizenship Behavior, organizational climate has a significant effect on OrganizationalCitizenship Behavior which is mediated by job satisfaction and work motivation does not have a significant effect on Organizational Citizenship Behavior which is mediated by job satisfaction for Indomaret employees in Buleleng District.